EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PENINGKATAN HASIL BELAJAR KOGNITIF SISWA SEKOLAH DASAR: STUDI KUASI-EKSPERIMEN - Rizky Kurniati; Elyas Djufri; Ana Fitrotun Nisa; Heri Maria Zulfiati (UNMUHBABEL Press, 2026)
This study aimed to examine the effectiveness of the Problem Based Learning (PBL) model in improving elementary school students’ cognitive learning outcomes. The research employed a quantitative approach with a quasi-experimental posttest-only control group design. The participants were fifth-grade students at an elementary school in Bandung, Indonesia, selected using purposive sampling technique, consisting of 20 students in the experimental group and 22 students in the control group. The experimental group was taught using the Problem Based Learning model, while the control group received conventional instruction. Data were collected through a written posttest consisting of 10 multiple-choice items, validated through expert judgment and empirically tested for validity and reliability (Cronbach’s Alpha = 0.749). Data were analyzed using descriptive statistics, an independent samples t-test, and effect size analysis. The results showed a significant difference in learning outcomes between the two groups (t = 2.49; p = 0.017). Students in the experimental group achieved higher mean scores than those in the control group. The effect size analysis produced a Cohen’s d value of 0.76, indicating a moderate to large effect. These findings suggest that the PBL model is effective in improving elementary school students’ cognitive learning outcomes and can serve as an alternative instructional strategy that promotes active student engagement in elementary education.